2021
DOI: 10.1016/j.biochi.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural modelling and thermostability of a serine protease inhibitor belonging to the Kunitz-BPTI family from the Rhipicephalus microplus tick

Abstract: rBmTI-A is a recombinant serine protease inhibitor that belongs to the Kunitz-BPTI family and that was cloned from Rhipicephalus microplus tick. rBmTI-A has inhibitory activities on bovine trypsin, human plasma kallikrein, human neutrophil elastase and plasmin with dissociation constants in nM range. It is characterized by two inhibitory domains and each domain presents six cysteines that form three disulfide bonds, which contribute to the high stability of its structure. Previous studies suggest that serine p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This feature allows them to maintain their protease-inhibitory activity over a wide range of temperatures and pH values. Indeed, the Kunitz peptide SdPI from the scorpion Lychas mucronatus [58] and BmTI-A from tick Rhipicephalus microplus [59] were shown to be thermostable, while Bm-SPI51 from the cocoon of the silkworm Bombyx mori is both heat-and pH-resistant [60]. Based on the CD spectra and residual trypsin activity levels, we revealed that HCIQ2c1, HCIQ4c7, and HMIQ3c1 are thermostable peptides retaining the conformation of the active molecules up to 90-100 • C, whereas the trypsin-inhibitory activity of HCIQ1c9 is reduced by up to 70% in the temperature range of 60-100 • C, an observation that was confirmed by the CD spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature allows them to maintain their protease-inhibitory activity over a wide range of temperatures and pH values. Indeed, the Kunitz peptide SdPI from the scorpion Lychas mucronatus [58] and BmTI-A from tick Rhipicephalus microplus [59] were shown to be thermostable, while Bm-SPI51 from the cocoon of the silkworm Bombyx mori is both heat-and pH-resistant [60]. Based on the CD spectra and residual trypsin activity levels, we revealed that HCIQ2c1, HCIQ4c7, and HMIQ3c1 are thermostable peptides retaining the conformation of the active molecules up to 90-100 • C, whereas the trypsin-inhibitory activity of HCIQ1c9 is reduced by up to 70% in the temperature range of 60-100 • C, an observation that was confirmed by the CD spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate hydrolysis was measured at 410 nm. The residual activity was calculated based on the results of three parallel experiments according to the following equation [60]: % = (1 − residual enzyme activity/enzyme activity without inhibitor) × 100…”
Section: Trypsin-inhibitory Activitymentioning
confidence: 99%
“…Has been corroborated that coiled-coil regions are important because they are strictly related to the correct assembly of the protein's final and functional structure (Linding et al, 2003). Some studies suggest that these regions have been known as linkers, probes, and inhibitors of protein-protein interactions (Bomediano Camillo et al, 2021;Watkins et al, 2015).…”
Section: Discussionmentioning
confidence: 99%